Methodology of the brodalumab assessment of hazards: a multicentre observational safety (BRAHMS) study. Issue 2 (1st February 2023) - Reilev, Mette; Jensen, Peter Bjødstrup; Ranch, Lise Skov; Egeberg, Alexander; Furu, Kari; Gembert, Karin; Hagg, David; Haug, Ulrike; Karlstad, Øystein; Reutfors, Johan; Schäfer, Wiebke; Schwartz, Sarina; et al.
Abstract : Introduction: Safe and effective pharmacological treatment is of paramount importance for treating severe psoriasis. Brodalumab, a monoclonal antibody against interleukin (IL) 17 receptor A, was granted marketing authorisation in the EU in 2017. The European Medicines Agency requested a postauthorisation safety study of brodalumab to address potential safety issues raised during drug development regarding major adverse cardiovascular events, suicidal conduct, cancer and serious infections. Methods and analysis: BRodalumab Assessment of Hazards: A Multinational Safety is a multicentre observational safety study of brodalumab running from 2017 to 2029 using population-based healthcare databases from Denmark, Sweden, Norway, Netherlands, Germany and three different centres in Italy. A distributed database network approach is used, such that only aggregate data are exchanged between sites. Two types of designs are used: a case-time-control design to study acute effects of transient treatment and a variation of the new user active comparator design to study the effects of transient or chronic treatment. As comparators, inhibitors of TNF-α, inhibitors of IL-12 and IL-23, and other inhibitors of cytokine IL-17A are included. In the self-controlled case-time-control design, the risk of developing the outcome of interest during periods of brodalumab use is compared within individuals to the risk in periods without use. In the active comparator cohort design, new users of brodalumab are identified and matched to new users of active comparators. Potential baseline confounders are adjusted for by using propensity score modelling. For outcomes that potentially require large cumulative exposure, an adapted active comparator design has been developed. Ethics and dissemination: The study is approved by relevant authorities in Denmark, Norway, Sweden, the Netherlands, Germany and Italy in line with the relevant legislation at each site. Data confidentiality is secured by the distributed network approach. Results will be published in peer-reviewed journals. Trial registration number: EUPAS30280.